Survey on Image Segmentation Techniques using Traditional and Soft Computing Techniques - Kumari, Roopa; Gupta, Neena (International Journal of Computer Sciences and Engineering, 2025)
Digital image processing plays an important role in computer technology. DIP has a variety of applications, image segmentation is one of the important application. Segmentation is a process of segment an image into different objects or parts. At present scenario, segmentation is an active research area. The issue of image segmentation is always of great concern as it enables the optimization in the extraction of the features and characteristics of the image. This paper presents a review of Traditional image segmentation techniques along with Soft computing Techniques